2021
DOI: 10.1007/s00423-021-02362-y
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art surgery for pancreatic cancer

Abstract: Background The d evelopment of surgical techniques and specialization and specifically complication management in pancreatic surgery have improved surgical outcomes as well as oncological results in pancreatic surgery in recent decades. Historical morbidity and especially mortality rates of up to 80% have decreased to below 5% today. This review summarizes the current state of the art in pancreatic cancer surgery. Methods The present literature and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
1
10
1
1
Order By: Relevance
“…Therefore, a formal pancreatic resection including lymphadenectomy may not be obligatory in many cases. Contrary, highly suspected malignancy (i.e., PDAC) is a contraindication to perform CP 22 . In our study, postoperative histopathology revealed PDAC in one patient.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Therefore, a formal pancreatic resection including lymphadenectomy may not be obligatory in many cases. Contrary, highly suspected malignancy (i.e., PDAC) is a contraindication to perform CP 22 . In our study, postoperative histopathology revealed PDAC in one patient.…”
Section: Discussioncontrasting
confidence: 48%
“…Contrary, highly suspected malignancy (i.e., PDAC) is a contraindication to perform CP. 22 In our study, postoperative histopathology revealed PDAC in one patient. Upon patient request no revision surgery was performed and adjuvant therapy was started.…”
Section: Discussionsupporting
confidence: 47%
“…The large-scale use of MIPS for PDAC also remains controversial for now, due to a lack of literature on the long-term outcomes. 91 , 93 , 101 …”
Section: Role Of Minimally-invasive Pancreatic Surgery In the Treatme...mentioning
confidence: 99%
“…The RFA procedure is an electrocautery-based technique that results in tissue necrosis. It has been used widely for managing unresectable primary as well as secondary liver cancer, where it has been previously reported by Nießen et al [ 8 ]. The local recurrence was primarily dependent on tumor size.…”
Section: Introductionmentioning
confidence: 99%